2020
DOI: 10.1016/j.ajo.2019.10.019
|View full text |Cite
|
Sign up to set email alerts
|

GUCY2D-Associated Leber Congenital Amaurosis: A Retrospective Natural History Study in Preparation for Trials of Novel Therapies

Abstract: The Wellcome Trust (099173/Z/12/Z), Moorfields Eye Hospital Special Trustees, Moorfields Eye Charity, Retina UK, Fight for Sight UK, and the Foundation Fighting Blindness (USA). Financial Disclosures: Michalis Georgiou and Michel Michaelides consult for MeiraGTx. The other authors have no financial disclosures. All authors attest that they meet the current ICMJE criteria for authorship. Zaina Bouzia and Michalis Georgiou contributed equally and should be considered equivalent authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 37 publications
1
46
1
Order By: Relevance
“…In the homozygous Gucy2e tm1Gar model, D 50 was >12 months (Figure 6), indicating very slow rod PR cell loss, while cone cell numbers decreased rapidly to 33% of controls in 5 weeks [191]. Cone loss with rod preservation has been observed in Leber congenital amaurosis cases linked to variants of the human Gucy2e ortholog, GUCY2D [192]. However, Gucy2e tm1Gar mice are not considered to model this disease because rod ERG function, though diminished, is still detectable [191].…”
Section: Category 02: Visual Transductionmentioning
confidence: 91%
“…In the homozygous Gucy2e tm1Gar model, D 50 was >12 months (Figure 6), indicating very slow rod PR cell loss, while cone cell numbers decreased rapidly to 33% of controls in 5 weeks [191]. Cone loss with rod preservation has been observed in Leber congenital amaurosis cases linked to variants of the human Gucy2e ortholog, GUCY2D [192]. However, Gucy2e tm1Gar mice are not considered to model this disease because rod ERG function, though diminished, is still detectable [191].…”
Section: Category 02: Visual Transductionmentioning
confidence: 91%
“…Clinical presentation includes severe congenital/early infancy visual loss, nystagmus, amaurotic pupils and a markedly abnormal or undetectable full-field electroretinogram (ERG) [ 1 ]. The most common causative genes are CEP290 [ 2 ], GUCY2D [ 3 ], CRB1 [ 4 ], and RPE65 [ 5 8 ] . In total, the reported LCA/EOSRD-associated genes (n = 25) account for approximately 70–80% of cases [ 6 , 7 ], with more genes yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to compare the phenotypes of these patients as they are of different ages (7-year-old boy and 42-year-old woman, respectively), and we did not have full data about the course of the disease in the infancy in the female patient. Studies on a group of 21 patients with molecularly confirmed LCA1 revealed the relatively preserved photoreceptor structure over a broad age range indicating a wide therapeutic window for gene therapy trials [ 27 ].…”
Section: Discussionmentioning
confidence: 99%